Conversations with Ghosts by Alex Tanous with Callum E. Cooper - McCormick, Donna (Journal of Scientific Exploration, 2015)
I was invited to review this book because of my association with Alex Tanous. For more than a decade, beginning in 1975, I worked as a researcher at the American Society for Psychical Research (ASPR) alongside Karlis Osis, the ASPR’s Research Director and Chester F. Carlson Research Fellow. During those years, Osis and I conducted a variety of experimental studies and field investigations; Alex Tanous participated as an unpaid subject in much of that research. Sadly, I am the sole survivor of our little team1 and, therefore, the last insider who could provide firsthand insight about the people and research activities of the ASPR during that era, and who could critically examine this book’s treatment of the same. The authorship of this book is credited to the psychic Alex Tanous, who died in 1990, approximately 23 years prior to the book’s publication. Using the designation of “with” (often employed by “ghostwriters,”2 no pun intended), co-authorship was credited to Callum Cooper who, at the time the book was written, was a doctoral candidate at the University of Northampton’s Centre for the Study of Anomalous Psychological Processes, Department of Psychology.